2018
DOI: 10.5812/ijem.55023
|View full text |Cite
|
Sign up to set email alerts
|

Waist Circumference to Height Ratio: Better Correlation with Fat Mass Than Other Anthropometric Indices During Dietary Weight Loss in Different Rates

Abstract: BackgroundThe first-line strategy for the treatment of obesity is weight loss (WL) through decreasing calorie intake. However, a diet that is capable of attenuating fat free mass decline following WL is preferred. Furthermore, it is required to choose proper measurements and appropriate obesity-assessment indices to monitor weight and body composition during WL program.MethodsA total of 68 adults with overweight and/or obesity underwent a WL program (rapid and slow WL). Dependent variables include: weight, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Traditionally, the use of dietary interventions has been shown as a priority method for losing BFP (12) . However, evidence has shown that energy restriction may decrease resting and total energy expenditure due to a reduction in LBM, which in turn stops BW decrements (13,14) . Indeed, Renzo et al (15) reported that women with NWO display lower RMR compared with lean, overweight and obese individuals due to the significant differences in LBM.…”
mentioning
confidence: 99%
“…Traditionally, the use of dietary interventions has been shown as a priority method for losing BFP (12) . However, evidence has shown that energy restriction may decrease resting and total energy expenditure due to a reduction in LBM, which in turn stops BW decrements (13,14) . Indeed, Renzo et al (15) reported that women with NWO display lower RMR compared with lean, overweight and obese individuals due to the significant differences in LBM.…”
mentioning
confidence: 99%
“…This index is closely related to metabolic risk factors and mortality, independent of body weight. 19,20 Body composition differs among all ethnic groups and different populations worldwide. Thus, what is the best way to assess the obesity associated with metabolic diseases using anthropometric indices is still controversial.…”
Section: Tuoms P R E S Smentioning
confidence: 99%
“…WHO defines obesity as an excessive accumulation of fat to the extent that health may be impaired (7) . Therefore, in addition to weight loss (WL) in general, preferential reduction of fat mass (FM) may be the best way to manage obesity and its complications (8) . As such, the relationships between FM and fat-free mass (FFM) during WL are worthy of consideration.…”
mentioning
confidence: 99%